Model calculation of liquid crystal dimers - Abulyaissova, L.K.; Alimbayeva, M.T.; Nurzhanova, G.K. (KSU publ, 2012)
The potential surface of internal rotation in the pair interaction between molecules of nematic liquid crystal with the general formula XC6H4OR (X = H, F, Cl, Br, CN, NO2 and R = CH2CCC6H5) has been investigated by ab initio methods in the RHF/6-31G(d) approximation. It is shown that the shape of the potential surface is modified for phenylpropargyl ethers of phenols with electron-donating substituents and unsubstituted ether, passing from a single molecule to molecular pair. However, ab initio calculations predict the same stable conformation for all examined ethers.
Keywords: potential surface; nematic liquid crystals; electron-donating substituents